Teaching Communities: An Autoethnographic Exploration of Engaging with Students in Extracurricular Programs - Dineen, Rachel; Ilett, Darren; Warner, Adrienne (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
While instruction librarians seek the most meaningful experiences for our students, sometimes we have to look beyond tradition to meet students where they are and where they feel a sense of belonging on campus. Through autoethnography we explore what it means to teach and learn with students in extracurricular communities, such as those in support programs for first-generation students and student-athletes. We reflect on how working with these communities has shaped us as teacher librarians, including our perceptions of belonging. While not always clear-cut, we argue that working with extracurricular communities brings benefits not addressed by traditional subject librarianship.